P227 Home NIV in COPD: A Real Life Study. (19th November 2012) - Naseer, R; Ghosh, D; Neep, A; Rodger, J; Johnson, O
Abstract : Introduction: Home NIV in selected patients with stable hypercapnic COPD has been shown to reduce hospital admissions. Randomised studies have produced conflicting evidence on its effect on quality of life and survival. High intensity ventilation has shown promise. However, most studies of NIV for COPD have been in highly selected patients in the research setting. We attempt to explore the impact of home NIV in a district hospital setting. Methods: All patients established on home NIV for COPD for at least 1 year were identified from NIV database. The primary outcomes were number of hospital admissions, length of hospital stay (LOS) and days requiring acute NIV during the 12 months before starting NIV and the 12 months after. Secondary outcomes were admission blood gases during these periods. Results: Thirty-seven patients were identified, 9 were excluded as COPD was not the primary diagnosis or records could not be traced. Twenty-eight patients (23 females) were included in the study (Age 63±9 years, BMI 34±10, FEV1 0.58±0.18, FEV1% predicted 27±10, FEV1/FVC 41±10). The mean IPAP and EPAP at 3 months were 21±3 and 7±3 cm of H2O Table 1 describes the results. Fourteen patients did not have any admissions after institution of NIV. Discussion and conclusion: Institution of home NIV significantly reduced admissions, hospital stay and need for acute NIV in a cohort of severe COPD patients with hypercapnia. Even though the decision to offer NIV was not based on any rigid criteria, but was a clinical decision based on blood gases, spirometry and admissions, these patients acted as their own controls. It is possible that following NIV, the patients received more home visits from our respiratory nursing team but as frequent attenders they were already receiving significant nursing input by the same nursing team in the community. The apparent lack of improvement in blood gases was probably due to the fact that only 11 patients had an admission ABG post NIV and only 4 of them more than once. This real life study shows a significant impact of home NIV in COPD in terms of admissions and hospital stay. Bigger studies are necessary to assess its longer term effect.